Why privacy keeps dying: the trouble with talk about the end of privacy. Issue 2 (1st February 2017) - John, Nicholas A.; Peters, Benjamin
ABSTRACT: It is a curious fact how much talk about privacy is about the end of privacy. We term this 'privacy endism, ' locating the phenomenon within a broader category of endist thought. We then analyze 101 newspaper articles between 1990 and 2012 that declare the end of privacy. Three findings follow. First, claims about the end of privacy point to an unusually broad range of technological and institutional causes. Privacy has been pronounced defunct for decades, but there has never been a near consensus about its causes. Second, unlike other endist talk (the end of art or history, etc.), privacy endism appears ongoing and not period specific. Finally, our explanation of the persistence and idiosyncrasy of claims to the end of privacy focuses on Warren and Brandeis's 1890 negative conception of privacy as 'the right to be let alone': namely, modern privacy talk has always been endist because the right to privacy was born out of the conditions for its violation, not its realization. The conclusion comments on implications of that basic proposition.